A Dispatchable Droop Control Method for PV Systems in DC Microgrids - Jiahua Ni; Bo Zhao; Arman Goudarzi; Yanjun Li; Ji Xiang (IEEE Access, 2023)
Along with the sustained growth of photovoltaic (PV) penetration, the PV generation is expected to be more active in DC microgrids rather than maximum power generation. The droop control methods are generally adopted to achieve power regulation at steady-state and passive power-sharing at transient state. However, the traditional $V-I$ droop based control methods can not realize voltage dispatch orders and require mode switching to prevent overload problem which increases control complexity and deteriorate the performance. To address this issue, this paper proposes a novel dispatchable droop control method. The proposed method utilizes a two-layer hierarchical control structure. The primary layer is $V-dp/dv$ droop control to achieve passive power-sharing at a smaller time scale. The secondary layer realizes power or voltage regulation based on the dispatch orders at a larger time scale. Moreover, with the $dp/dv$ as the control variable, the proposed method realizes seamless mode switching and has the ability to roughly indicate the power margin of PVs, which is critical for dispatching PVs. Several case scenarios are conducted in hardware-in-loop tests to validate the feasibility and effectiveness of the proposed control strategy on DC microgrids.